Age in life course - Czerniawska, Olga (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
The text present reflections concerning calendar age perceived not only as an objective category but especially as a subjective category from the perspective of the end of life – old age, coupled with experience from the whole life, including childhood experiences. The author refers to the age stratification theory, social clock idea and the concept of the social age elaborated by Helena Radlińska. She emphasizes the fact that the historical feeling of being old has changed over time The author also draws attention to the complexity of the perception of the old age of other people, age-related epithets, biographical memory, heart memory present in the experience of old people.